2017
DOI: 10.1038/srep40881
|View full text |Cite
|
Sign up to set email alerts
|

HO-1 inhibits preadipocyte proliferation and differentiation at the onset of obesity via ROS dependent activation of Akt2

Abstract: Excessive accumulation of white adipose tissue (WAT) is a hallmark of obesity. The expansion of WAT in obesity involves proliferation and differentiation of adipose precursors, however, the underlying molecular mechanisms remain unclear. Here, we used an unbiased transcriptomics approach to identify the earliest molecular underpinnings occuring in adipose precursors following a brief HFD in mice. Our analysis identifies Heme Oxygenase-1 (HO-1) as strongly and selectively being upregulated in the adipose precur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 80 publications
3
38
0
Order By: Relevance
“…In further support of these observations, mouse obese ASCs exhibited a reduced capability for adipogenic differentiation associated with a decreased expression of related genes insulin receptor substrate 1 (IRS1), IRS2 and FABP4 compared with mouse control ASCs . In addition, it was demonstrated that the heme oxygenase‐1 inhibited proliferation and differentiation of preadipocytes at the onset of obesity via reactive oxygen species dependent activation of Akt/PKB (protein kinase B) in obese mouse models . By contrast, the data from a transcriptomic profile analysis displayed an increased commitment to an adipocyte‐like phenotype , supported by another report showing that obese ASCs conferred an enhanced potential of adipogenic differentiation associated with increased mRNA expression of the adipogenic markers PPARγ and FABP4 .…”
Section: Dysfunction Of Adipose‐derived Mesenchymal Stem Cells In Obementioning
confidence: 82%
“…In further support of these observations, mouse obese ASCs exhibited a reduced capability for adipogenic differentiation associated with a decreased expression of related genes insulin receptor substrate 1 (IRS1), IRS2 and FABP4 compared with mouse control ASCs . In addition, it was demonstrated that the heme oxygenase‐1 inhibited proliferation and differentiation of preadipocytes at the onset of obesity via reactive oxygen species dependent activation of Akt/PKB (protein kinase B) in obese mouse models . By contrast, the data from a transcriptomic profile analysis displayed an increased commitment to an adipocyte‐like phenotype , supported by another report showing that obese ASCs conferred an enhanced potential of adipogenic differentiation associated with increased mRNA expression of the adipogenic markers PPARγ and FABP4 .…”
Section: Dysfunction Of Adipose‐derived Mesenchymal Stem Cells In Obementioning
confidence: 82%
“…Heme increases lipid accumulation, promotes cell enlargement, induces over-expression of adipogenic genes, such as PPARG, C/EBP-α and adipocyte protein 2 (aP2), and downregulates adiponectin [32,34,54]. The increase in heme combined with increased ROS leads to adipocyte dysfunction by promoting inflammatory infiltration of macrophages and other inflammatory molecules, increases in circulating levels of glucose and a decrease in cytoprotective molecules, such as adiponectin and HO-1 [33,34,55]. Chronic oxidative stress leads to further adipocyte dysfunction, and can increase lipid accumulation [33,34].…”
Section: The Na/k-atpase Oxidant Amplification Loop and Ho-1: Implicamentioning
confidence: 99%
“…Chronic oxidative stress leads to further adipocyte dysfunction, and can increase lipid accumulation [33,34]. The induction of HO-1 in disease models of obesity provide an antioxidant setting, which increases mitochondrial fusion and improves the secretory profile of adipocytes (i.e., increased adiponectin expression and decreased inflammatory cytokine release) [33,55]. HO-1 upregulation has also been linked to increased insulin sensitivity, improvement in phosphorylation of insulin receptors, and improved adipocyte function [35].…”
Section: The Na/k-atpase Oxidant Amplification Loop and Ho-1: Implicamentioning
confidence: 99%
See 1 more Smart Citation
“…ROS are highly reactive molecules, which makes them essential second messengers, participating in many cell signaling pathways including proliferation, differentiation, immune response and apoptosis (Simon et al 1998, Griendling et al 2000. At physiological levels in adipose tissue, ROS participate in metabolic homeostasis as well as preadipocyte proliferation through an insulin-dependent pathway (Castro et al 2016, Wagner et al 2017 and in adipocyte differentiation through H 2 O 2 -induced cAMP response element-binding protein beta (C/EBP-beta) DNA-binding activity, along with C/EBP-beta phosphorylation (Lee et al 2009, Tormos et al 2011.…”
Section: Adipose Tissue Oxidative Stress In Obesity Ros Signaling In mentioning
confidence: 99%